Rancang Bangun Game Adventure 3D Kesehatan Gigi - Naufal Luqmanul Hakim; Cindy Taurusta; Arif Senja Fitrani (LPPM STIKI MALANG, 2024)
Since good practices in childhood will influence adult habits, dental health education should start early. Until recently, the only way to get information about dental health care and good and bad food choices for teeth was through lectures and pamphlets. The traditional approach is considered boring, unnecessarily visualized, and not difficult enough for children to understand. Dr. Rizza Dwi Prasetya from K24 Dental Care Lamongan says that one of the most important things to maintain good dental growth and health is to instill the value of dental care in children from an early age. One way to do this is by creating a 3D adventure game for Android smartphones that teaches about oral health. The Multimedia Development Life Cycle (MDLC) approach, which consists of six stages-ideation, design, material collection, assembly, testing, and distribution-was used in making this application. With an indicator of 81%